Mentorship expectations differences across generations: A study of South African black women - Kanyuchi, Amantle (Graduate School of Business (GSB), 2025)
This research investigates the differing mentorship expectations among African-Black women across three generational cohorts: the Struggle Generation (ages 42–61), the Transition Generation (ages 29–41), and the Born Free Generation (ages 22–28). Recognizing mentorship as a vital coping strategy in workplace environments, the study employs qualitative research to explore how factors like historical context, technology, and intersectionality shape these expectations. The study employs a qualitative methodology to explore mentorship relationship expectations among different generational cohorts of African black women in South Africa. Through in- depth interviews with participants from the Struggle, Transition, and Born Free Generations, the research uncovers nuanced experiences and expectations surrounding mentorship. A semi-structured format facilitated open dialogue, allowing participants to share their beliefs and motivations. Data collection adhered to ethical guidelines, ensuring confidentiality, while thematic and narrative analysis identified key patterns and themes. This approach captures diverse perspectives, contributing to a deeper understanding of mentorship dynamics within this demographic. Findings reveal that while the cohorts share a common understanding of mentorship, they differ in preferred formats, key factors for effective relationships, and desired qualities in mentors and mentees. The Struggle Generation balances professional and familial roles, the Born Free Generation seeks digital and informal avenues, and the Transition Generation emphasises proactive engagement. Ultimately, this dissertation highlights that for mentorship to deliver on its promise of fostering both professional growth and personal empowerment, it needs to be dynamic and evolve with the changing needs of generations. The insights underscore the need for tailored mentorship programs that address the diverse needs of African-Black women.